Analisis Peningkatan Efektivitas Pendidikan dan Pelatihan Awak Angkutan Umum Mikrotrans di DKI Jakarta - Nur Achmad Jabrial (Sekolah Tinggi Manajemen Transportasi (STMT Malahayati Jakarta), 2024)
This study aims to analyze and improve the effectiveness of education and training for Microtrans public transportation crews in DKI Jakarta. The study was conducted on March 16-18, 2023 using a questionnaire given to 21 respondents, including the Leaders and Members of Committees/Institutions/Government Organizations and Public Transportation Company Cooperatives as Microtrans Operators in DKI Jakarta. The data obtained from the questionnaire revealed that several indicators showed that the effectiveness of education and training for Microtrans public transportation crews still needed to be improved. Based on the results of the analysis, several important findings were found: Punctuality of Training: As many as 20.62% of Microtrans public transportation crews have not implemented punctuality in Training. Training achievement targets: As many as 28.55% of Microtrans public transportation driver crews have not achieved the Training target. Implementation of Training results: As many as 20.62% of Microtrans public transportation driver crews have not implemented the Training results properly. Benefits of Training: As many as 23.80% of Microtrans public transportation driver crews have not utilized the Training optimally. Work performance after attending the training: As many as 31.73% of Mikrotrans public transportation driver crews have not achieved the expected work performance after attending the training. good Post-training behavior: As many as 30.14% of Mikrotrans public transportation driver crews have not shown good behavior after attending the training. Based on these findings, it is recommended to make improvements and enhancements in the education and training program for Mikrotrans public transportation crews in DKI Jakarta. Improvement efforts can be made by increasing the punctuality of training, identifying and meeting training achievement targets, improving the implementation of training results, increasing the benefits of training, improving work performance after attending training, and encouraging good behavior after training. Thus, it is hoped that the effectiveness of education and training for Mikrotrans public transportation crews can be improved, thereby providing a better contribution to improving safety, smoothness, comfort, reliability, and public services in DKI Jakarta.